2009
DOI: 10.48550/arxiv.0908.2336
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Universal description for different types of polarization radiation

D. V. Karlovets,
A. P. Potylitsyn

Abstract: When a charged particle moves nearby a spatially inhomogeneous condensed medium or inside it, different types of radiation may arise: Diffraction radiation (DR), Smith-Purcell radiation (SPR), Transition radiation (TR), Cherenkov radiation (CR) etc. Along with transverse waves of radiation, the charged particle may also generate longitudinal oscillations. We show that all these phenomena may be described via quite simple and universal approach, where the source of the field is the polarization current density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…In our theoretical estimations we will follow the recent papers of Karlovets and Potylitsyn [18,19] where authors have shown a simple and elegant method of the Maxwell's equations solution that makes it possible to simulate the characteristics of any type of polarization radiation (including transition radiation, diffraction radiation, CR, SPR) appearing simultaneously. The term "polarization radiation" clearly shows a nature of the radiation that is a polarization of a target (grating) material by electromagnetic field of the traveling charged particle.…”
Section: Theoretical Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…In our theoretical estimations we will follow the recent papers of Karlovets and Potylitsyn [18,19] where authors have shown a simple and elegant method of the Maxwell's equations solution that makes it possible to simulate the characteristics of any type of polarization radiation (including transition radiation, diffraction radiation, CR, SPR) appearing simultaneously. The term "polarization radiation" clearly shows a nature of the radiation that is a polarization of a target (grating) material by electromagnetic field of the traveling charged particle.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…The term "polarization radiation" clearly shows a nature of the radiation that is a polarization of a target (grating) material by electromagnetic field of the traveling charged particle. In the cited articles [18,19] it was shown that the method developed gives well known results for transition radiation, diffraction one, CR and SPR that are just different "kinematic" cases of the polarization radiation.…”
Section: Theoretical Modelmentioning
confidence: 99%
See 3 more Smart Citations